Oral Contraceptive Use and Increased Risk of Stroke: A Dose–Response Meta-Analysis of Observational Studies - Li, Feng; Zhu, Lin; Zhang, Jie; He, Hongye; Qin, Yueqi; Cheng, Yuan; Xie, Zongyi (Frontiers in Neurology, 2019)
Background: Oral contraceptives (OCPs) use might increase the risk of stroke in women. We examined a possible dose-response relation between OCPs use and the risk of stroke in young and middle-aged women. Methods: A search of PubMed and EMBASE databases was performed. We selected observational studies that reported odds ratios (ORs) with 95% confidence intervals (CIs) for the risk of stroke in users of OCPs. A two-stage dose-response analysis was conducted using the random-effects model and the restricted spline model. Results: A total of 18 studies were included which involved 2,143,174 participants and 11,661 cases of stroke including ischemic stroke (IS), hemorrhagic stroke (HS) and stroke of unknown origin. The pooled ORs of total stroke were 1.19 (95% CI, 1.16-1.23) for every 10-μg increment in estrogen dosage, 1.20 (95% CI, 1.05-1.37) for every 5-year increment in duration of OCPs use, 0.82 (95% CI, 0.68-0.98) for every 5-year increment in duration of OCPs cessation. The ORs of IS were 1.20 (95% CI, 1.17-1.22) for estrogen dosage, 1.24 (95% CI, 1.04-1.49) for duration of OCPs use, 0.78 (95% CI, 0.67-0.92) for duration of OCPs cessation. The ORs of HS were 1.10 (95% CI, 1.04-1.16) for estrogen dosage, 1.13 (95% CI, 0.93-1.36) for duration of OCPs, 0.71 (95% CI, 0.55-0.92) for duration of OCPs cessation. The pooled ORs of total stroke from prospective studies 1.12 (95% CI, 1.01-1.24) were lower than that from retrospective studies 1.30 (95% CI, 1.01-1.67). Conclusions: The higher estrogen dosage significantly increased the risks of total stroke, IS and HS, respectively. The longer duration of OCPs use significantly increased the risks of total stroke and IS, but its effects on HS risk was marginal. The longer duration of OCPs cessation significantly decreased the risks of total stroke, IS and HS, respectively. These findings affirm the contribution of estrogen dose and duration of OCPs use to the increased risk of stroke, which may be used as important reference for the instruction of OCPs use and the prevention and management of cerebrovascular diseases.